Determination of Thrombogenicity Levels of Various Antiphospholipid Antibodies by a Modified Thrombin Generation Assay in Patients with Suspected Antiphospholipid Syndrome - Bradáčová, Pavla; Slavík, Luděk; Skoumalová, Adéla; Úlehlová, Jana; Kriegová, Eva; Manukyan, Gayane; Friedecký, David; Piskláková, Barbora; Ullrychová, Jana; Procházková, Jana; Hluší, Antonín (International journal of molecular sciences, 2022)
Antiphospholipid syndrome (APS) is a hypercoagulable state accompanied by the presence of heterogeneous antiphospholipid antibodies (aPL), which nonspecifically affect hemostasis by the presence of lupus anticoagulans (LA), anticardiolipin antibodies (aCL), antibodies against β2-glycoprotein-I (anti-β2GPI), but also non-criteria antibodies such as antibodies against β2-glycoprotein-I domain I (anti-DI), anti-phosphatidylserine/prothrombin (anti-PS/PT), anti-annexin V, and many others. The main target of the antibodies is the activated protein C (APC) system, the elimination of which can manifest itself as a thrombotic complication. The aim of this study was to determine the thrombogenicity of antibodies using a modified protein C-activated thrombin generation assay (TGA) on a group of 175 samples suspected of APS. TGA was measured with/without APC and the ratio of both measurements was evaluated (as for APC resistance), where a cut-off was calculated ≤4.5 (90th percentile) using 21 patients with heterozygous factor V Leiden mutation (FV Leiden heterozygous). Our study demonstrates the well-known fact that multiple positivity of different aPLs is a more severe risk for thrombosis than single positivity. Of the single antibody positivity, LA antibodies are the most serious (p value < 0.01), followed by aCL and their subgroup anti-DI (p value < 0.05). Non-criteria antibodies anti-annexin V and anti-PT/PS has a similar frequency occurrence of thrombogenicity as LA antibodies but without statistical significance or anti-β2GPI1 positivity. The modified TGA test can help us identify patients in all groups who are also at risk for recurrent thrombotic and pregnancy complications; thus, long-term prophylactic treatment is appropriate. For this reason, it is proving increasingly beneficial to include the determination antibodies in combination with modified TGA test.
Keywords: lupus anticoagulants; Female; antikardiolipinové protilátky; Antibodies, Antiphospholipid; thrombosis; ženské pohlaví; anti-β2-glycoprotein-I; thrombogenicity; chemiluminescence analysis; Prothrombin; lidé; trombóza; beta-2-glykoprotein I; anti-cardiolipin; beta 2-Glycoprotein I; těhotenství; fosfatidylseriny; protrombin; FV Leiden heterozygous; antifosfolipidový syndrom; Antiphospholipid Syndrome; Protein C; ELISA; anti-phosphatidylserine/prothrombin; protein C; seronegative APS; anti-annexin V; Antibodies, Anticardiolipin; thrombin generation assay; Thrombosis; Phosphatidylserines; antiphospholipid syndrome; antifosfolipidové protilátky; Pregnancy; trombin; Thrombin; Humans